2016
DOI: 10.1158/1078-0432.ccr-15-3059
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Estrogen Receptor Signaling with Fulvestrant Enhances Immune and Chemotherapy-Mediated Cytotoxicity of Human Lung Cancer

Abstract: Purpose The conversion of tumor cells from an epithelial to a mesenchymal-like phenotype, via a process designated as the epithelial-mesenchymal transition (EMT), is known to mediate tumor resistance to a variety of cell death inducers, including cytotoxic effector immune cells. The goal of this study was to identify and potentially repurpose FDA-approved compounds capable of reducing mesenchymal features of human lung carcinoma cells, which could be used in combination with immunotherapies or chemotherapeutic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
(49 reference statements)
3
37
0
Order By: Relevance
“…Mesenchymalization and the molecular drivers of the process, including the transcription factors Snail, Slug, Twist, and brachyury, have been linked to advanced tumor stage (36)(37)(38), presence of metastases (39), and poor prognosis in numerous cancer types (40)(41)(42). Additionally, mesenchymalization has been associated with resistance to anticancer therapies, including chemotherapy (43,44), small-molecule-targeted therapies (45,46), and to lysis by immune effector cells (47)(48)(49)(50). In the case of breast cancer, this phenomenon has been linked to tumor progression in preclinical models (51) and with patient tumor samples (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymalization and the molecular drivers of the process, including the transcription factors Snail, Slug, Twist, and brachyury, have been linked to advanced tumor stage (36)(37)(38), presence of metastases (39), and poor prognosis in numerous cancer types (40)(41)(42). Additionally, mesenchymalization has been associated with resistance to anticancer therapies, including chemotherapy (43,44), small-molecule-targeted therapies (45,46), and to lysis by immune effector cells (47)(48)(49)(50). In the case of breast cancer, this phenomenon has been linked to tumor progression in preclinical models (51) and with patient tumor samples (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…who demonstrated that high levels of the EMT‐related factor Brachyury reduced the susceptibility of carcinoma cells not only to CTLs, but also to NK cells, lymphokine‐activated killer, FAS, and TRAIL‐induced cell death. In a recent report investigating the lung cancer setting, the same group further found a potential role for estrogen receptor α in promoting both Mes characteristics and resistance to immune‐mediated cytotoxicity (Hamilton et al ., ). By contrast, the study of López‐Soto et al .…”
Section: Emt‐mediated Immune Resistance To Nk Cellsmentioning
confidence: 97%
“…Recent reports suggested that two widely used compounds, the EGFR inhibitor erlotinib, and fulvestrant, an antagonist of ER, may be efficient at decreasing Mes features of lung cancer cells as well as for improving their lysis by the immune effector cells (Dominguez et al ., ; Hamilton et al ., ). In addition, as suggested in our previous studies, it could be interesting to target autophagy when Mes carcinoma cells exhibit an autophagic state (Akalay et al ., ).…”
Section: Targeting Emt To Attenuate Immunoresistance and Improve Suscmentioning
confidence: 97%
“…This dose-escalation phase I study was conducted to demonstrate the safety of MVA-brachyury-TRICOM and to determine its ability to generate brachyury-specific CD4 + or CD8 + T cells in patients with advanced cancer. Future phase II studies of this vaccine will be based on the preclinical rationale of vaccine studies in combination with checkpoint inhibitor monoclonal antibodies (MAbs), immune modulators, inhibitors of immune entities, and combinations of these (6,3943). …”
Section: Introductionmentioning
confidence: 99%